Engineering Perspective and Economic Evalution of The Synthesis Zinc Oxide Nanopowder by Co-Precipitation Method - Nandiyanto, Asep Bayu Dani; Nurahmawati, Yeni (Jurnal Scientia Indonesia, 2015)
The purpose of this study is to evaluate the engineering and economic evaluation of the manufacture of zinc oxide (ZnO) Â nanopowder by coprecipitation method. Economic evaluation is carried out with several parameters such as: GPM (Gross Profit Margin), PBP (Payback Period), and CNPV (Cumulative net present value) based on simple mathematical calculations using the Microsoft Excel Application. From the project feasibility test it was found that the project suffer a financial loss if the tax paid was 100% and the selling price was less than 90%. The project can produce as many as 1,1017 tons/year of ZnO nanopowder. ZnO nanopowder production can provide benefits up to 76%. Economic evaluations show positive results because the payback period (PBP) occurs around the 4th year, and profits will continue to increase until the 20th year. Thus, the production of ZnO nanopowder can be considered a lucrative project.